(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Recently new opportunities are emerging for improving the way patients with Haemophilia A are treated. Among these opportunities, efmoroctocog alfa is a first-in-class recombinant factor VIII-Fc fusion protein (rFVIIIFc) produced by recombinant DNA technology with an extended half-life compared with conventional FVIII preparations. The available evidence coming from an Italian HTA report indicates that efmoroctocog alfa provides an effective alternative to conventional FVIII preparations (including standard rFVIIIs) for the management of Haemophilia A. Moreover, by reducing the frequency of injections required, it has the potential to reduce treatment burden, and hence improve adherence to prophylaxis and patient Quality-of-Life.